Integrasi Augmented Reality dalam Festival Seni Budaya sebagai Model Penguatan Administrasi Pendidikan Berbasis Komunitas - Elyakim Nova Supriyedi Patty; I Nyoman Yoga Sumadewa; Melati Rosanensi (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2026)
This community service program aimed to develop a model of community-based educational administration through the integration of Augmented Reality in a cultural arts festival. The program was conducted in Sigar Penjalin Village, North Lombok Regency, involving a local traditional art group as the main partner. The primary issues included the absence of formal institutional management, limited use of digital technology, and low community participation in cultural preservation. A participatory action research approach combined with community development was applied, involving stages of needs assessment, capacity building, technology development, and festival implementation. The results showed the establishment of a community-based art studio, improved managerial and technological skills among participants, and the development of interactive Augmented Reality media for traditional dance promotion. The cultural festival successfully increased community engagement and served as a practical platform for implementing non-formal education management. This program demonstrated that integrating digital technology with community-based cultural activities could strengthen educational administration and support sustainable cultural preservation.